Family Guidance and Counseling: A Holistic Analysis of Married Couples' Emotional Intelligence in Strengthening Family Resilience - Andrepati, Raraswara; Dartina, Vina; Fitrah, Syari (IKIP Siliwangi, 2025)
This study aims to determine the role of emotional intelligence in husbands and wives in strengthening family resilience. This research employs a qualitative research method using a case study approach. The study was conducted from January to June 2024, with five informants as the subjects. Data collection methods included in-depth interviews, observations, and documentation. Data analysis was carried out using a holistic analysis approach. The findings reveal that the roles and responsibilities of husbands and wives include the husband's duty to serve as the spiritual leader of the household, provide financial support for his wife and children, ensure safety, offer protection, and care for the family. The study concludes that emotional intelligence is crucial in strengthening family resilience. By cultivating emotional intelligence, families can build greater resilience, enhance happiness, and achieve shared goals for a more meaningful family life. The contribution of this research serves as a foundation for developing marriage counseling programs, emotional intelligence training, and family education initiatives.